Meningkatkan Kemandirian Belajar dalam pembelajaran Pendidikan Agama Katolik dengan Model Discovery learning AKU MEMILIKI KEMAMPUAN Fase D Kelas VII SMP Negeri 1 Girsang Sipangan Bolon - Masduita Damanik (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research was carried out as a form of solving student problems in increasing student learning independence. The independence of student learning in learning is closely related to the quality and ability of the teacher as a designer of learning in the classroom, as well as implementing learning in the classroom. This research was carried out so that students were active in learning Catholicism at SMP Negeri 1 Girsang Sipangan Bolon, Simalungun Regency, learning Catholicism was less attractive to some students because it was not in the State Examination and the number of students was minimal. So the authors conducted research to increase student learning independence at SMP Negeri 1 Girsang Sipangan Bolon with the Discovery Learning learning model